Turkish Hybotidae (Diptera: Empidoidea): description of six new species with additional data - Zouhair, Laila; Grootaert, Patrick; Gençer, Lütfiye; Kettani, Kawtar (Zootaxa, 2025)
Six species belonging to the genera Platypalpus Macquart, Tachydromia Meigen and Drapetis Meigen are described as new for science from the Asian part of Turkey (Anatolia): P. sivasensis sp. nov., P. hirfanlicus sp. nov., P. latemoides sp. nov., P. durulmusensis sp. nov., T. sivasensis sp. nov. and D. incompletoides sp. nov. The species P. nigritarsis Fallén is recorded herein for the first time from Turkey. We report for the first time the occurrence of Platypalpus bohousi Barták & Kubík, P. kirtlingensis Grootaert, P. longiseta Zetterstedt and Crossopalpus setiger Loew in previously unreported biogeographical areas within the country with detailed data on their distribution. All new species are described and illustrated.